Construction of Attitude Scale: Attitude of Schoolteachers Towards Teaching Profession (Sudurpaschim Spectrum, 2023)
The progress of the nation is based on the competencies of the citizens, and the overall development of the person depends on the effectiveness of the educational system implemented in the country. The teacher is a key factor in the implementation of educational programs. Without a favorable attitude toward the teaching profession, teachers cannot do well in the teaching profession. Regarding this context, this study was conducted to construct an attitude scale to measure the attitude of schoolteachers towards the teaching profession. Steps of standardization of the test were adopted to construct a reliable and valid tool. Piloting was made in the Indo-Nepalese context. A quantitative research design was used in this study. A draft of 50 statements was designed, and 40 were selected on the basis of expert judgment. A sample of 374 schoolteachers from five districts of Nepal and India was selected using a random sampling technique. Eight statements were rejected based on item analysis and respondents' suggestions. A standardized attitude scale was developed comprising 32 statements, which were again categorized into eight factors on the basis of factor analysis. Various reliability coefficients ranging from .80 to .87 were found. For interpretation of the results, z-score and percentile norms were developed. This test will be beneficial to researchers who are interested in identifying the attitudes of schoolteachers in the Indo-Nepalese context.